EXPEDIENTE - Tavares de Barros, Fernando Hélio; Löff Machado , Lucas; Sipavicius Seide, Márcia (Revista de Letras Norte@mentos, 2022)
Expediente do Dossiê Temático: Onomástica, da Revista de Letras Norte@mentos.